2001
DOI: 10.2741/lijnen
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting in hemostasis. alpha2-antiplasmin

Abstract: Apha2-antiplasmin (AP), the main physiological plasmin inhibitor in mammalian plasma, is a 70 kDa single chain serpin (serine proteinase inhibitor) with reactive site peptide bond Arg-Met. It inhibits plasmin very rapidly (second-order inhibition rate constant of = 2 x 107 M-1.s-1) following formation of an inactive 1:1 stoichiometric complex. The high reaction rate requires the presence of a free active site and free lysine-binding site(s) in plasmin. The pathophysiologic relevance of AP is suggested by the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…21,22,27,29 -31 Homozygous ␣ 2 -antiplasmin-deficient mice do not exhibit abnormal bleeding, but do demonstrate diminished thrombosis after vascular injury and accelerated lysis of experimental pulmonary emboli. 32,33 These results suggest that the main in vivo function of ␣ 2 -antiplasmin is to regulate circulating plasmin activity and intravascular fibrinolysis. Dewerchin et al studied mice with combined deficiency of PAI-1 and ␣ 2 -antiplasmin in several bleeding and thrombosis models and compared doubledeficient mice to mice with isolated deficiency of each factor to study the relative roles of these inhibitors in regulating fibrinolysis in vivo.…”
Section: Insights Into Regulation Of Intravascular Fibrinolysis From mentioning
confidence: 83%
“…21,22,27,29 -31 Homozygous ␣ 2 -antiplasmin-deficient mice do not exhibit abnormal bleeding, but do demonstrate diminished thrombosis after vascular injury and accelerated lysis of experimental pulmonary emboli. 32,33 These results suggest that the main in vivo function of ␣ 2 -antiplasmin is to regulate circulating plasmin activity and intravascular fibrinolysis. Dewerchin et al studied mice with combined deficiency of PAI-1 and ␣ 2 -antiplasmin in several bleeding and thrombosis models and compared doubledeficient mice to mice with isolated deficiency of each factor to study the relative roles of these inhibitors in regulating fibrinolysis in vivo.…”
Section: Insights Into Regulation Of Intravascular Fibrinolysis From mentioning
confidence: 83%
“…Discussion α 2 -AP is a serine protease inhibitor that rapidly sequesters plasmin into a stable inactive complex and thereby regulates fibrinolysis [17,18]. However, Kawashita et al reported that α 2 -AP also enhances dendritic growth in hippocampal neurons independently of the fibrinolytic system [24].…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitymentioning
confidence: 97%
“…Significant bleeding tendency is observed in patients with homozygous α 2 -AP deficiency, highlighting its physiological significance [17,18]. Heterozygous patients have mild or no bleeding tendency [17,18]. The role of α 2 -AP in bone metabolism and in the pathogenesis of osteoporosis remains unknown, although several studies suggest various activities besides inhibition of fibrinolysis [19,20].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations